Creative Process-Based Digital Teaching Materials to Increase Poetry Writing Creativity of High School Students - Suherli Kusmana; Jimat Susilo; Mira Nuryanti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Teaching materials play an essential role in improving the success of the learning process. Traditionally, teachers use teaching materials in learning, often textbooks, which are generally presented based on the author's thoughts and interpretations of the learning outcomes. Teachers have not widely used teaching materials developed as a person's literary activity process and have not  utilised technology as a scaffold for achieving activity skills. Likewise, when teaching poetry texts to high school students, teachers still have difficulty increasing their creativity in writing poetry by only utilizing teaching materials from available textbooks. This study aims to develop teaching materials for poetry texts for high school students that are developed based on the creative process of productive poets and presented using digital technology. The study began by conducting interviews with productive poets about the creative process of producing poetry, studying the needs of teaching materials for teachers, and analyzing learning outcomes. The next step is to prepare a design of teaching materials according to the stages of the creative process in writing poetry as a basis for development and presenting it in digital form. Teaching materials are validated through expert judgment, namely by language experts, literature experts, Indonesian language and literature learning experts, and learning technology experts. Furthermore, digital poetry text teaching materials were tested through classroom learning in eight meetings at Senior High School (SMA) and Madrasah Aliyah (MA). This study produced a digital poetry text teaching material model developed based on a creative process. The validation results stated that the digital poetry text teaching material model for SMA/MA was declared very valid based on the assessment components of material or content, presentation of material, language, and graphics. The trial of teaching materials in SMA and MA shows that digital poetry text teaching materials can improve students' creative abilities in writing poetry. In addition, students' activities are more responsive and enthusiastic in participating in learning. The results of this study can contribute to providing literary teaching materials that can improve students' creativity in writing poetry.